Important considerations in treating children, adolescents and young adults with colorectal carcinoma. (August 2013) - Furman, Wayne L; Tricoli, James V
SUMMARY Colorectal carcinoma (CRC) in children, adolescents and young adults under 30 years of age is rare. When it occurs in these young people, is this just an 'adult' cancer occurring in a young patient or is it a different disease? How should these patients be managed? Here, we review what is known about the epidemiology and clinical presentation of CRC in children, adolescents and young adults, as well as the current model for CRC development to provide a framework for questioning whether CRC in these young patients is the same disease as that seen in their older adult counterparts. In addition, we will summarize the clinical options described in the peer-reviewed literature to provide a basis for management decisions of these young patients.